The Impact of the COVID-19 Pandemic on the Health Systems of the European Union Member States: An Empirical Study - Katarzyna MIKOLAJCZYK; Joanna NIZNIK (Communications of International Proceedings, 2025)
The aim of this article is to evaluate the changes in the performance of the health systems of European Union countries during the COVID-19 pandemic, measured by different health system indicators. The main research hypothesis states that the scope and depth of change depended on the condition of the system in the pre-pandemic period, and the low performance of the system necessitated urgent action to improve its efficiency. The research methods are based on inductive reasoning combined with a study of the literature on the subject, a search of Internet resources and available databases. On the basis of information included in the aforementioned sources, the most important indicators and indices that are used to assess health systems are identified and publications on healthcare systems performance during the COVID-19 pandemic, in which the authors use statistical models are presented. In the empirical part the changes in selected healthcare systems indices, mainly Global Health Security Index, are analysed and used for clustering and ranking EU countries, based on their similarities.
Keywords: health care system; COVID-19; pandemic